Inter-hospital transfer in patients with acute myocardial infarction in China: Findings from the improving care for cardiovascular disease in China-acute coronary syndrome project - Hu, Danqing; Hao, Yongchen; Liu, Jun; Yang, Na; Yang, Yiqian; Sun, Zhaoqing; Zhao, Dong; Liu, Jing (Frontiers in Cardiovascular Medicine, 2022)
Background: Little is known about the current scenario of inter-hospital transfer for patients with acute myocardial infarction (AMI) in China. Methods: From November 2014 to December 2019, 94,623 AMI patients were enrolled from 241 hospitals in 30 provinces in China. We analyzed the pattern of inter-hospital transfer, and compared in-hospital treatments and outcomes between transferred patients and directly admitted patients. Results: Of these patients, 40,970 (43.3%) were transferred from hospitals that did not provide percutaneous coronary intervention (PCI). The proportion of patients who were transferred from non-PCI hospital was 46.3% and 11.9% (P < 0.001) in tertiary hospitals and secondary hospitals, respectively; 56.2% and 37.3% (P < 0.001) in hospitals locating in low-economic regions and affluent areas, respectively. Compared with directly admitted patients, transferred patients had lower rates of reperfusion for STEMI (57.8% vs. 65.2%, P < 0.001) and timely PCI for NSTEMI (34.7%vs. 41.1%, P < 0.001). The delay for STEMI patients were long, with 6.5h vs. 4.5h from symptom onset to PCI for transferred and directly admitted patients, respectively. The median time-point was 9 days for in-hospital outcomes. Compared with direct admission, the hazard ratios and 95% confidence intervals associated with inter-hospital transfer were 0.87 (0.75–1.01) and 0.87 (0.73–1.03) for major adverse cardiovascular events and total mortality, respectively, in inverse probability of treatment weighting models in patients with STEMI, and 1.02 (0.71–1.48) and 0.98 (0.70–1.35), respectively, in patients with NSTEMI. Conclusion: More than 40% of the hospitalized AMI patients were transferred from non-PCI-capable hospitals in China. Further strategies are needed to enhance the capability of revascularization and reduce the inequality in management of AMI.